2016
DOI: 10.1039/c5gc01952d
|View full text |Cite
|
Sign up to set email alerts
|

Cosolvent pretreatment in cellulosic biofuel production: effect of tetrahydrofuran-water on lignin structure and dynamics

Abstract: The deconstruction of cellulose is an essential step in the production of ethanol from lignocellulosic biomass. However, the presence of lignin hinders this process. Recently, a novel cosolvent based biomass pretreatment method called CELF (Cosolvent Enhanced Lignocellulosic Fractionation) which employs tetrahydrofuran (THF) in a single phase mixture with water, was found to be highly effective at solubilizing and extracting lignin from lignocellulosic biomass and achieving high yields of fermentable sugars. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(104 citation statements)
references
References 57 publications
4
99
0
1
Order By: Relevance
“…Furthermore, the angle distribution near −152° is narrower in 75% ethanol solution than in pure ethanol. This effect is in qualitative agreement with the results of Smith et al, who studied the conformation of lignin polymers of up to 60 units in water‐tetrahydrofuran (THF) mixtures . In their study, they found that mixed solvents facilitate the solvation of lignin molecules, which, instead, in pure water adopt a crumbled globular‐like shape, with a considerably reduced SASA.…”
Section: Resultssupporting
confidence: 90%
“…Furthermore, the angle distribution near −152° is narrower in 75% ethanol solution than in pure ethanol. This effect is in qualitative agreement with the results of Smith et al, who studied the conformation of lignin polymers of up to 60 units in water‐tetrahydrofuran (THF) mixtures . In their study, they found that mixed solvents facilitate the solvation of lignin molecules, which, instead, in pure water adopt a crumbled globular‐like shape, with a considerably reduced SASA.…”
Section: Resultssupporting
confidence: 90%
“…THF has ab oiling point of 66 8 8Ca nd ad ensity of 0.8892 gcm À3 .T he main use of THF is for the synthesis of poly(tetramethylene ether) glycol (PTMEG;8 0-88 %o f world annual production), as as olvent in chemical synthesis and processes (mainly for polymerization reactions), and as ac osolvent in pretreatment processes for biomass. [334] The most widely used industrial process for the production of THF involves the acid-catalyzed dehydration of 1,4-butandiol [335] (Scheme 12 b) which can be produced through the acetylene/ formaldehyde Reppe process or by the hydrogenation of the renewable platform chemical succinic acid, derived from glucose. [37,336] Additionally,m any improvements have been established for the direct hydrogenation of succinic acid to THF in one step (Scheme 12 a).…”
Section: Tetrahydrofuran (Thf)mentioning
confidence: 99%
“…THF is mainly used for the production of poly(tetramethylene ether) glycol as a chemical solvent [31,83]. It is also being considered as a biofuel candidate.…”
Section: Tetrahydrofuranmentioning
confidence: 99%